MANAJEMEN PEMBELAJARAN BERBASIS PROJEK PADA PENDIDIKAN ANAK USIA DINI - Hanita Hanita; Yoyon Suryono; Puji Yanti Fauziah (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2023)
Learning management is a reference for teachers in carrying out a learning implementation. Project-based learning also has steps and implementation procedures. So in this study we want to examine in depth how to implement project learning in education, especially in early childhood education. The research method used is literature review and will use the PRISMA checklist to determine the selection of studies that have been found and adapted to the objectives of the literature review. The results of the research Project-based learning management in early childhood education has different procedures and procedures. The same concept is only at the planning, implementation and evaluation stages, which are indeed stages in the learning process. From several researches it is still found that project-based learning from the point of view of the initial originator of the project method, namely William H. Kilpatrick, is still lacking. The conclusions on the implementation of project learning in early childhood are diverse. But still through planning, implementation and evaluation. However, this is still considered far from the steps that were originally applied by the originator of the project method, namely William H. Kilpatrick. This change was due to the many theoretical developments of William H. Kilpatrick's project method.